Pengaruh Leverage, Profitabilitas, Capital Intensity, Manajemen Laba Terhadap Penghindaran Pajak - Ahmad Rifai; Suci Atiningsih (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2019)
The purpose of this study is knowing the effect of leverage, profitability, capital intensity, and earnings management on tax avoidance. The period of this study is 5 (five) years, from 2013 to 2017. The data used are secondary data. The population is mining sector companies listed on the Indonesia Stock Exchange from 2013 to 2017 with a total of 47 companies. The sample selection is determined by the purpose sampling method and the samples used are 11 companies with a total of 55 data. The data analysis method is multiple linear regression. The results of the study that profitability, capital intensity, and earnings management negatively affect tax avoidance. Leverage has no effect on tax avoidance